Malvidin alleviates mitochondrial dysfunction and ROS accumulation through activating AMPK-α/UCP2 axis, thereby resisting inflammation and apoptosis in SAE mice - Zhao, Panpan; Li, Xiaomin; Yang, Qiankun; Lu, Yingzhi; Wang, Guanglu; Yang, Haitao; Dong, Jingquan; Zhang, Honggang (Frontiers in Pharmacology, 2023)
This study aimed to explore the protective roles of malvidin in life-threatened sepsis-associated encephalopathy (SAE) and illustrate the underlying mechanism. SAE mice models were developed and treated with malvidin for subsequently protective effects evaluation. Malvidin restored neurobehavioral retardation, declined serum S100β and NSE levels, sustained cerebrum morphological structure, improved blood-brain barrier integrity with elevated tight junction proteins, and decresed evans blue leakage, and finally protect SAE mice from brain injury. Mechanically, malvidin prevented cerebrum from mitochondrial dysfunction with enhanced JC-1 aggregates and ATP levels, and ROS accumulation with decreased lipid peroxidation and increased antioxidant enzymes. UCP2 protein levels were found to be decreased after LPS stimulation in the cerebrum and BV-2 cells, and malvidin recovered its levels in a ROS dependent manner. In vivo inhibition of UCP2 with genipin or in vitro interference with siRNA UCP2 both disrupted the mitochondrial membrane potential, decreased ATP levels and intensified DCF signals, being a key target for malvidin. Moreover, dorsomorphin block assays verified that malvidin upregulated UCP2 expression through phosphorylating AMPK in SAE models. Also, malvidin alleviated SAE progression through inhibition of ROS-dependent NLRP3 inflammasome activation mediated serum pro-inflammatory cytokines secretion and mitochondrial pathway mediated apoptosis with weakened apoptosis body formation and tunel positive signals, and decreased Bax, cytochrome C, caspase-3 and increased Bcl-2 protein levels. Overall, this study illustrated that malvidin targeted AMPK-α/UCP2 axis to restore LPS-induced mitochondrial dysfunction and alleviate ROS accumulation, which further inhibits NLRP3 inflammasome activation and mitochondrial apoptosis in a ROS dependent way, and ultimately protected SAE mice, providing a reference for the targeted development of SAE therapeutics.